1993
DOI: 10.1002/jlb.53.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Role of PAF in the allergic pleurisy caused by ovalbumin in actively sensitized rats

Abstract: Selective platelet-activating factor (PAF) antagonists and autodesensitization to this lipid were used to investigate the role of PAF in antigen-induced pleurisy in the rat. Pleural inflammation was triggered by the intrathoracic (i.t.) injection of ovalbumin (12 micrograms/cavity) into animals actively sensitized 14 days before. Successive daily i.t. injections of PAF (1 microgram/cavity) led to selective autodesensitization, which was apparent after the third injection and maximal after the fifth. The PAF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
4
11
0
Order By: Relevance
“…According to previously published data, OVA challenge induced a marked increase in total leukocyte numbers in the pleural cavity within 24 h, with a significant accumulation of eosinophils (Martins et al, 1993). Based on that data, we examined leukocyte influx into the pleura cavity, and our results show that AEBv treatment attenuated polymorphonuclear accumulation, mainly eosinophils influx, in the allergic pleurisy without a significant change in mononuclear cell recruitment.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…According to previously published data, OVA challenge induced a marked increase in total leukocyte numbers in the pleural cavity within 24 h, with a significant accumulation of eosinophils (Martins et al, 1993). Based on that data, we examined leukocyte influx into the pleura cavity, and our results show that AEBv treatment attenuated polymorphonuclear accumulation, mainly eosinophils influx, in the allergic pleurisy without a significant change in mononuclear cell recruitment.…”
Section: Discussionsupporting
confidence: 63%
“…Allergic pleurisy was performed as described by Martins et al (1993) with modifications. Mice were actively sensitized by dorsal subcutaneous injection of a mixture containing 50 mg OVA and 5 mg aluminum hydroxide in a final mixture volume of 0.2 mL.…”
Section: Allergic Pleurisymentioning
confidence: 99%
“…These changes are followed by neutrophil influx, peaking from 4 to 8 h, and mononuclear cell and eosinophil influx, first noted at 8 h but peaking from 12 to 24 h postallergen challenge (Lima et al, 1997). All these events were clearly sensitive to the systemic treatment with dexamethasone, whereas histamine and 5-hydroxytryptamine receptor antagonists inhibited plasma leakage without altering leukocyte infiltration (Martins et al, 1993). In our first set of experiments, we have shown that the local administration of peptide Ac2-26 reduced plasma leakage and neutrophil and eosinophil emigration into the rat pleural space, leaving intact the mononuclear cell enrichment caused by allergen challenge.…”
Section: Discussionmentioning
confidence: 96%
“…Supporting these observations, treatment with SC displayed an inhibitory effect on edema induced by histamine and 5-HT, but failed to inhibit PAF-induced paw edema. The participation of PAF in edema forma- tion and eosinophil mobilization in allergic inflammation has been reported (20,21) and the lack of effect of the SC extract on PAFinduced edema and the participation of the other mediators in the triggering of allergic paw edema may account for discrete effect of the SC extract on allergic paw edema. These results suggest that the SC extract can be much more effective in inhibiting reactions whose mechanism depends on the release of histamine and of 5-HT.…”
Section: Discussionmentioning
confidence: 97%